Verstärkt die ,,Große Rezession“ das Auseinanderdriften der Wettbewerbsfähigkeit in der EU? - Fritz Breuss (FIW - Research Centre International Economics, 2009)
At its 10th anniversary the EMU had to stand the baptism of fire caused by the Great Recession 2009. By and large it mastered this test. The introduction of the Euro, however, has brought to light the latent weaknesses in competitiveness of some member states of the Euro area, consisting up to now mostly of old EU member states. Shortly after the EU enlargement in 2004 and 2007 Cyprus, Malta, Slovakia and Slovenia introduced the Euro. Out of 27 EU member states already 16 countries belong to the Euro area. In the near future one can expect a further enlargement of the Euro area. The permanent diversion of competitiveness between the new and the old EU member states could, however, evolve into a big problem with respect to the coherence of the enlarged Euro area, pursuing a common monetary policy. Here we focus particularly on the differing competitiveness - measured by the relative unit labour costs or the real exchange rates - within the enlarged union. Conclusions are drawn with respect to the current "Great Recession".
Keywords: E52; F15; F31; F41; 330; EMU; International Competitiveness; Great Recession